Quantifying the Association Between Code Status Discussions and Outcomes in Critically Ill Older Adults Admitted to the Intensive Care Unit (ICU): A Retrospective Cohort Study - Jessica T. Kent; Rishi Ghosh (Emergency Care and Medicine, 2025)
Background: “Do Not Resuscitate” (DNR) status has been implicated as an independent risk factor for mortality in patients admitted to the ICU. The implications of DNR status in older, critically ill patients for whom these conversations are often most relevant are less known. Objective: To determine the relationship between code status and mortality in a subset of critically ill, older ICU patients. Methods: Retrospective cohort study of critically ill older adults as defined by an APACHE II score ≥20 and age ≥70, admitted to the ICU at a large community hospital in Ontario from 1 January 2013 to 31 December 2018. Results: Of 613 patients admitted to the ICU, 163 met the inclusion criteria. Of these, 64 (39.3%) had a DNR order, while the remaining 99 (60.7%) did not and were considered full code. We found a strong association between DNR status and mortality (OR 2.61; 95% CI 1.33 to 5.09). Patients with a DNR order stayed fewer days in the ICU (7.7 days (±3.6) vs. 9.9 days (±8.3)) and used fewer resources than similarly ill patients who were full code with no difference in discharge morbidity. Patients with a DNR order had lower average costs of hospital and ICU admissions in comparison to patients who were full code (CAD 49,589.10/pt. vs. CAD 59,704.70/pt. (Canadian dollars)). Conclusions: Among critically ill, older ICU patients, DNR status is strongly associated with in-hospital mortality. Those in the full code group used more resources, resulting in higher costs of hospitalization without any difference in discharge morbidity.